USE OF "DIDACTIC" METHODS IN PRIMARY SCHOOLS, IN THE EDUCATIONAL PROCESS (Conferencea, 2022)
In this article, the design of the lesson process with didactic games, interactive game methods, "Didactic" games based on methods, the main types of lesson games, general game theory and students in primary school " Didactic ”games focus on the environment, interest in life, challenges, how to overcome obstacles and develop critical thinking skills.